PERLINDUNGAN HUKUM TERHADAP KORBAN FIRST TRAVEL DALAM TINDAK PIDANA PENCUCIAN UANG - Febrianti Syafitri; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Legal protection for victims to regain their rights in the First Travel case is urgently needed forvictims of money laundering by First Travel. Indeed, the state has a legal basis to confiscate the victim's assets,but the state is deemed not entitled to take the victim's assets because the source of the money is not from thestate and the money that is the subject of the crime of money laundering is the victim's money, not state money.This can clarify the weakness of the criminal justice system in regards to recovering losses to victims, not eventhe state benefiting from the judge's decision.The purpose of this study is to determine the impact of the Supreme Court decision Number 3096 K /Pid.sus / 2018 on First Travel victims, to find out how the state should protect victims and the rights of victimsof money laundering by First Travel and to find out what legal remedies can be made. carried out by FirstTravel victims after the verdict. The research method used in this thesis uses normative legal researchmethods, namely legal research that examines statutory regulations and legal principles.From the research, there are three main points that can be concluded. First, the impact of theSupreme Court Decision Number 3096 K / Pid.Sus / 2018 on victims of money laundering by First Travel isthat victims feel very disadvantaged by the state because their rights to their money belong to the state and theweaknesses of the criminal justice system that do not consider the interests of and victim rights. Second, thestate should protect victims by providing legal assistance to incapacitated victims and becoming a forum forthe community to obtain protection, and raising the Umrah for First Travel victims or returning half of thevictim's money. Author's suggestion, First, it is hoped that in the future in cases of money laundering such asFirst Travel, the money that is the subject of this crime comes from public money. The judge should be wiser inweighing the decision to transfer the money to the state which should be returned to the victim who feelsaggrieved. Second, in the future the state should protect its citizens who are victims of the crime of moneylaundering and the state is expected to restore the rights of the victims.Keywords: Victims, Crime, Money Laundering